Celebrity Physical Attractiveness Effect on Consumer Buying Behavior - Rizwan Khalid; Tehreem Yasmeen (University of Islam Malang, 2019)
Nowadays, the use of celebrity as brand endorsements is increasing. Celebrity is considered to be the fastest and safest way for a brand to develop an association and a bond in consumer minds. This study aimed to analyze the impact of a celebrity physical attractiveness on consumer buying behavior. This study only focuses on the buying intention of mobile phone product. Data was gathered from college (both private and public) undergraduate by questionnaires with an individual's age between 17 to 30 years as the target respondent. The reason in selecting those students with specific age is because they are the target consumer of the specific product that has been chosen as the research object. The researcher used simple random sampling as a sampling technique with 376 respondents and regression analysis is used to model the relationship between variable. This study concluded that there is a positive impact between the physical appearance of celebrity to purchase intention. There are a no different perception from gender, ages, institution type, and education background point of view regarding the attractiveness of celebrity physical and their intention to buy.